PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP, DISIPLIN DAN TANGGUNG JAWAB SISWA TINGKAT SEKOLAH DASAR - Retno Nurwidiyati (STKIP PGRI SITUBONDO, 2021)
The purpose of this study was to find out how students' understanding of concepts, disciplines and responsibilities could be improved by applying the Think Pair Share (TPS) model. The research method used is classroom action research which is carried out in two cycles, where each cycle consists of two meetings. The research subjects were 31 students of SDN Tanahwulan Maesan Bondowoso class Vb. The research instrument in the form of observation sheets and written tests was analyzed using qualitative descriptive analysis techniques. The indicator of the success of this classroom action research uses the minimum completeness criteria target (KKM) that has been set, namely 70 with classical completeness of 94% or 29 students. From the results of the study it was found that the average level of completeness of the students' conceptual understanding of social studies material continued to increase from the pre-cycle conditions of 52%, cycle 1 was 84% ​​and cycle 2 was 100%. In the discipline aspect, there was also an increase in the score from 71 in cycle 1, increasing to 86 in cycle 2. In the aspect of student responsibility, the score increased, namely 72 in cycle 1 and 85 in cycle 2. So it can be concluded that the application of the TPS learning model can improve understanding of students' concepts, disciplines and responsibilities